Laboratory measurements of ultrasonic velocities in CO2 saturated brines - Lebedev, M.; Bilenko, O.; Mikhaltsevitch, Vassili; Pervukhina, M.; Gurevich, B. (2013)
The acoustic velocities in CO2-saturated brines were investigated and compared with velocities measured in pure brines in the range of temperatures (30-70°C), pressures (2-38 MPa) and salinities (0 -100,000 ppm). It has been found that CO2 dissolution significantly changes the acoustic properties of brine. This change can be accounted for by a simple linear empirical equation.